2009
DOI: 10.1159/000280586
|View full text |Cite
|
Sign up to set email alerts
|

The Aromatase Inhibitor Fadrozole and the 5-Reductase Inhibitor Finasteride Affect Gonadal Differentiation and Gene Expression in the Frog <i>Silurana tropicalis</i>

Abstract: Aromatase (cyp19) and the 5α- and 5β-reductases (srd5alpha and srd5beta) are important enzymes for vertebrate sexual development. We investigated the effects of inhibition of cyp19 by fadrozole (FAD), and srd5alpha and srd5beta by finasteride (FIN) during anuran larval development. Chronic exposures of Silurana (Xenopus) tropicalis from Nieuwkoop-Faber stage 12 until stage 60 were performed using either 2 µM FAD or 25 µM FIN. Histological analysis of exposed metamorphic frogs revealed that both treatments indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…Finasteride significantly decreased hepatic srd5alpha2 and srd5beta mRNA levels in metamorphic S. tropicalis tadpoles (NF 60) and in whole larvae (NF 46) [Langlois et al, 2010]. Interestingly, the transcriptional regulation of srd5alpha3 mRNA was not affected by finasteride treatment in S. tropicalis in any tissue or developmental stage studied [NF 60 brain, present study; NF 60 liver Duarte-Guterman et al, 2009; NF 46 whole larvae Langlois et al, 2010]. Srd5alpha3 is a newly discovered enzyme and its regulation and function have not yet been fully explored [Tamura et al, 2007;Uemura et al, 2008], especially not in frogs.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Finasteride significantly decreased hepatic srd5alpha2 and srd5beta mRNA levels in metamorphic S. tropicalis tadpoles (NF 60) and in whole larvae (NF 46) [Langlois et al, 2010]. Interestingly, the transcriptional regulation of srd5alpha3 mRNA was not affected by finasteride treatment in S. tropicalis in any tissue or developmental stage studied [NF 60 brain, present study; NF 60 liver Duarte-Guterman et al, 2009; NF 46 whole larvae Langlois et al, 2010]. Srd5alpha3 is a newly discovered enzyme and its regulation and function have not yet been fully explored [Tamura et al, 2007;Uemura et al, 2008], especially not in frogs.…”
Section: Discussionmentioning
confidence: 64%
“…Tadpoles of Silurana tropicalis were exposed to finasteride (25 M ) dissolved in ethanol (EtOH; 0.05% final concentration) and fadrozole (2 M ) dissolved in water from Nieuwkoop-Faber (NF [Nieuwkoop and Faber, 1994]) stage 12 until stage 60, along with their respective controls (EtOH and water controls) as previously described in Duarte-Guterman et al [2009]. At the end of the exposure, brains were dissected and stored at -80 ° C. Homogenization and disruption of individual brain samples was achieved using an MM301 Mixer Mill (Retsch, Newton, Pa., USA) at 20 Hz for 3 min.…”
Section: Animals and Exposuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Another inhibitor, fadrozole, induced masculinization of gonad tissues in X. laevis [Miyata and Kubo, 2000]. Fadrozole was also used in S. tropicalis [Duarte-Guterman et al, 2009;Olmstead et al, 2009]. In this species, when applied at 2 μ M from stage 12 to stage 60, 55% of the individuals differentiated as males, 15% were intersex having testicular oocytes, and 30% were females.…”
Section: Importance Of Steroidsmentioning
confidence: 99%
“…Recently, adverse effects of using finasteride have become well established and data suggests that, in humans, it not only impairs sexual function, but also that it is associated with male breast cancer, various skin conditions, and depression, while in rodents, finasteride is linked to erectile dysfunction and change in prostate tissue histoarchitecture (reviewed in Traish, 2012). Aquatic amphibian species exposed to this 5a-reductase inhibitor also showed disrupted spermatogenesis, intersex animals, and a female biased sex ratio (Duarte-Guterman et al, 2009;Urbatzka et al, 2009). At the molecular level, gene expression endpoints have shown that finasteride alters the mRNA levels of gonadotropins-, androgen-, and thyroid hormone-related genes in the Western clawed metamorphosing frogs (Silurana tropicalis; Duarte-Guterman et al, 2009;Urbatzka et al, 2009;Langlois et al, 2011).…”
Section: Introductionmentioning
confidence: 99%